2016
DOI: 10.1016/j.imr.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Spirogyra neglecta inhibits the absorption and synthesis of cholesterol in vitro

Abstract: BackgroundSpirogyra neglecta (SN) has many nutritional benefits and it is commonly used to ameliorate different human conditions including inflammation, gastric ulcer, hyperglycemia, and hyperlipidemia. However, the mechanism of the hypocholesterolemic effect of SN still remains unclear. Therefore, the present study was aimed to evaluate the effect of SN extract particularly on cholesterol absorption and synthesis mechanisms.MethodsFor cholesterol absorption, the uptake of cholesterol was measured by using tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…Pancreatic cholesterol esterase is an enzyme which hydrolyses cholesterol esters, so inhibition of pancreatic cholesterol esterase can reduce cholesterol absorption and may be useful for therapeutics for controlling cholesterol [ 25 ]. Moreover, the reduction of micelle formation is a target for lowering blood cholesterol level [ 21 ]. This study evaluated nipa palm vinegar for its total phenolic content and the presence of phenolic compounds as well as determined its ability to inhibit pancreatic lipase, inhibit cholesterol esterase, and inhibit cholesterol micellization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cholesterol esterase is an enzyme which hydrolyses cholesterol esters, so inhibition of pancreatic cholesterol esterase can reduce cholesterol absorption and may be useful for therapeutics for controlling cholesterol [ 25 ]. Moreover, the reduction of micelle formation is a target for lowering blood cholesterol level [ 21 ]. This study evaluated nipa palm vinegar for its total phenolic content and the presence of phenolic compounds as well as determined its ability to inhibit pancreatic lipase, inhibit cholesterol esterase, and inhibit cholesterol micellization.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol micelles served as a model system for in vitro cholesterol micellization and were prepared according to a previous method [ 21 ]. In brief, the micelle solution (2 mM cholesterol, 1 mM oleic acid, and 2.4 mM phosphatidylcholine) was dissolved in methanol and then dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…SNE was dissolved in sterile water and administered orally by gavage once daily for 14 d as previously report. 29) The protocol of LPS-induced inflammation is summarised in Table 1.…”
Section: Chemicalsmentioning
confidence: 99%
“…27) In vivo studies indicated that this species has several beneficial effects, including anti-gastric ulcer, antihyperglycaemia and anti-hyperlipidaemia. 28,29) However, the information concerning effect of SNE on LPS-induced renal inflammation and its mechanisms remain unclear. This study, therefore, aimed to determine the effect of SNE on renal function, renal organic anion and cation transporter function and its mechanisms involved in experimental LPS-induced inflammation in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds in the CCW extract were further quantitated by high-performance liquid chromatography with diode array detection and a mass spectrometry detector (HPLC-DAD/MSD) (8). Briefly, phenolic compounds were separated using an Agilent 1100 series HPLC system (Agilent Technologies, Germany), equipped with a LiChroCART Stainless Steel Purospher STAR RP-18E column (150 mm × 4.6 mm, particle size 5 μm) (Merck, Germany) and a diode array detector recording at 270, 330, 350 and 370 nm.…”
Section: Analyses Of Phytochemicals In Ccw Extractmentioning
confidence: 99%